From Entity Description to Semantic Analysis: The Case of Theodor Fontane’s Notebooks - Martin de la Iglesia (OpenEdition, 2015)
Within the last few decades, TEI has become a major instrument for philologists in the digital age, particularly since a set of mechanisms has recently been incorporated which facilitates the encoding of genetic editions. Editors use the XML syntax while aiming to preserve the quantity and quality of old books and manuscripts and publish many more of them online, mostly under free licenses. Scholars all over the world are now able to use huge datasets for further research. There are now many digital editions available, but only a few tools to analyze them. This article explores how web technologies (XML and related technologies as well as JavaScript) can be used to enrich the forthcoming edition of Theodor Fontane’s notebooks with data-driven visualizations of named entities and how at the same time applications can be built on these visualizations which are reusable for other edition projects in the TEI world. Because of the density and historical scope of references to named entities and the variety of entity types, Fontane’s notebooks lend themselves to advanced methods of semantic analysis.